A retrospective analysis of antimicrobial resistance in pathogenic Escherichia coli and Salmonella spp. isolates from poultry in Uganda. Issue 1 (1st January 2021) - Kakooza, Steven; Muwonge, Adrian; Nabatta, Esther; Eneku, Wilfred; Ndoboli, Dickson; Wampande, Eddie; Munyiirwa, Damian; Kayaga, Edrine; Tumwebaze, Maria Agnes; Afayoa, Mathias; Ssajjakambwe, Paul; Tayebwa, Dickson Stuart; et al.
ABSTRACT: There are increasing reports of antimicrobial treatment failures for bacterial diseases of poultry in Uganda. The paucity of data on antimicrobial resistance (AMR) of pathogenic bacteria in Uganda is a major setback to AMR control. This study investigated the occurrence of fowl typhoid, colibacillosis, and AMR in associated pathogens from 2012 to 2018. Laboratory records from the Central Diagnostic Laboratory (CDL), a National Veterinary Diagnostic Facility located at Makerere University, were reviewed. Archived isolates of the causative bacteria for the two diseases were also evaluated for AMR. The frequencies of the two disease conditions, their clinical and necropsy presentations and the demographic data of the diagnostic samples were summarized from the records. Archived bacterial isolates were revived before antimicrobial susceptibility testing. This was done on Mueller Hinton agar using the disk diffusion method, against 16 antimicrobials of medical and veterinary importance according to the Clinical Laboratory Standards Institute guidelines. A total of 697 poultry cases were presented for bacteriological investigations in the review period. Colibacillosis and salmonellosis had prevalence rates of 39.7% (277/697) and 16.2% (113/697), respectively. A total of 63 and 92 isolates of Escherichia coli and Salmonella spp., respectively, were archived but 43 (68.3%) E. coli and 47 (51.1%) Salmonella spp. isolates were recovered and evaluated for AMR. Multidrug resistance was more frequent in E. coli (38; 88.4%) than salmonellae (25; 53.2%), ( p < 0.001). The high prevalence of colibacillosis, salmonellosis and the AMR of associated pathogens warrants immediate institution of appropriate disease control measures.